Concrete city : Material flows and urbanization in West Africa - Choplin, Armelle, 1978- (Hoboken, USA: Wiley, 2023)
"Concrete City: Material Flows and Urbanisation in West Africa delivers a theoretically informed, ethnographic exploration of the African urban world through concrete. Emblematic of frenetic and capitalistic urban development, this pervasive material is shaping contemporary urban landscapes and societies across West Africa and transforming the region's links to the world. Concrete stands and circulates at the heart of major financial investments, political powers, and environmental debates. As a result, it has come to epitomize values of modernity and success, and has redefined social practices, forms of dwelling, and popular imaginaries. The book invites readers to follow bags of cement as they travel from industrial production plants to construction sites along the 1000-kilometer urban corridor that links Abidjan to Accra, LomeÌ, Cotonou and Lagos. This cement traverses the lives of industrial tycoons, entrepreneurs and political stakeholders, as well as the ordinary men and women who plan, build, and dream of the Concrete City. In this innovative exploration of the urban life of concrete, Armelle Choplin delivers an incisive reflection on the material limits to the world's sustainable urban future."--
Includes index.
Keywords: Urbanization -- Africa, West; Sociology; Cement industries -- Africa, West; Cement -- Social aspects -- Africa, West; Cement -- Economic aspects -- Africa, West